Would you like to supersize your car? The effect of environmental subsidies on emissions - Ilona Tsanko (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
I study the impact of subsidies for Plug-in hybrid vehicles (PHEV) on carbon emissions. I show that subsidizing innovations without considering consumer behavior can harm the environment. I provide descriptive evidence on charging instances of PHEV and combine it with a structural model of demand for new passenger vehicles to evaluate the market outcomes had subsidies for PHEV not been in place. I show that PHEV subsidies were used by consumers to purchase larger and heavier vehicles and that consumers of PHEV seldom charge their vehicle. Taking into account the observed consumer behavior, I find that the elimination of subsidies for PHEV would have led to a yearly reduction of 167,139 tons of carbon emissions which are equivalent to the yearly carbon emissions 52,916 households emit due to energy consumption.
Keywords: D12; H23; H71; Q48; Q58; 330; Environmental regulation; Substitution; Carbon emissions; Automobiles; Demand estimation